Effects of Black Soldier Fly Larva Meal Oil in the Diet on Production Performance, Feed Cost, and Egg Quality of Laying Hens - Nonok Supartini; Puspita Sovie Juniar; Nisa Bejawati; Hariadi Darmawan; Sumarno (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2026)
This study assessed the production performance, economics, and egg quality of laying hens fed with 0%, 4%, 8%, and 12% Black Soldier Fly larval meal oil or maggot meal oil (MMO). Forty-eight Hy-Line Brown hens (50–60 weeks old) were allocated to four treatments (three replicates of four hens) in a completely randomized design over 30 days. Feed intake, hen-day production (HDP), feed conversion ratio (FCR), and income over feed cost (IOFC) were measured, alongside external and internal egg quality. MMO inclusion up to 12% did not significantly alter feed intake, HDP, or FCR (P > 0.05), though 8% MMO yielded the highest intake (120.1 g/head/day) and HDP (93.8%), and 12% MMO achieved the best FCR (1.13). IOFC rose at an MMO level, peaking at Rp 45,340 for 12% MMO. All egg quality traits, including shape index, weight, shell strength, air-cell depth, albumen and yolk indices, and Haugh Units, remained within Grade A standards. These results indicate that MMO can be used up to 12% of the diet without compromising production or egg quality while improving economic returns, and this study recommends an inclusion of 8% MMO to optimize production efficiency and profitability.